Perceptual Experiences of (Depicted) Absence - Voltolini, Alberto (JoLMA)
At least since Sorensen (2008) and Farennikova (2013), an important debate has been raised as regards whether one can experientially perceive absences. Three main positions have been discussed: radical perceptualism, cognitivism, and metacognitivism. In this paper, first of all, I want to claim that perceptualism can be maintained in a moderate form, once one explains the proper role that the relevant expectations play, as weakly cognitively penetrating one’s perception of absence in its phenomenal difference from a previous perceptual experience. Moreover, I want to claim that a similar result can be applied to pictorial perceptual experiences of absences, once one takes pictorial experience as a genuine yet sui generis perceptual seeing-in experience.